A history of mining in the Bathurst area, northern New Brunswick, Canada - William M. Luff (Canadian Institute of Mining, Metallurgy and Petroleum, 1995)
"The Bathurst area has recorded mining production as early as 1837, although the bulk of the production has come in recent years. Production has been mainly from the well-known massive sulphide deposits, but vein, gossan, and a variety of other deposits have also been mined. This paper summarizes the history of the mined deposits, along with tonnages and grades produced. A number of ""firsts"" have been noted in the Bathurst area. The A Zone deposit, located in the Heath Steele area, was the first in the world discovered using airborne electromagnetic methods. Heap leaching of gold from the gossan zone at Caribou was the first operation of its kind in Canada. The Keymet mine was the first base metal (lead-zinc) mine in New Brunswick. For the past few years, the Brunswick No. 12 mine has been one of the largest zinc mines in the world.IntroductionThe Bathurst area (Fig. 1) first had mining production in 1837 when copper was mined from a deposit on the Nepisiquit river (MacKenzie, 1958). The majority of the production, however, has been in recent years from massive sulphide deposits, but there are also other significant operations. . Table 1 is a summary of Bathurst area mineral production, showing concentrator feed tonnages and mill feed grades. The table does not include peat deposits, sand and gravel, dimension stone or rock quarries. Figure I is a general geology map of the Bathurst area, indicating deposit locations. The deposits are divided into four categories: massive sulphide, vein, gossan and other. The deposits in each category are described in chronological order of exploitation."